Heterologous Biosynthesis, Modifications and Structural Characterization of Ruminococcin-A, a Lanthipeptide From the Gut Bacterium Ruminococcus gnavus E1, in Escherichia coli - Ongey, Elvis L.; Giessmann, Robert T.; Fons, Michel; Rappsilber, Juri; Adrian, Lorenz; Neubauer, Peter (Frontiers in Microbiology, 2018)
Ruminococcin A (RumA) is a lanthipeptide with high activity against pathogenic clostridia and is naturally produced by the strict anaerobic bacterium Ruminococcus gnavus E1, isolated from human intestine. Cultivating R. gnavus E1 is challenging, limiting high-quality production, further biotechnological development and therapeutic exploitation of RumA. To supply an alternative production system, the gene encoding RumA-modifying enzyme (RumM) and the gene encoding the unmodified precursor peptide (preRumA) were amplified from the chromosome of R. gnavus E1 and coexpressed in Escherichia coli. Our results show that the ruminococcin-A lanthionine synthetase RumM catalysed dehydration of threonine and serine residues and subsequently installed thioether bridges into the core structure of a mutant version of preRumA (preRumA*). These modifications were achieved when the peptide was expressed as a fusion protein together with GFP, demonstrating that a larger attachment to the N-terminus of the leader peptide does not obstruct in vivo processivity of RumM in modifying the core peptide. The leader peptide serves as a docking sequence which the modifying enzyme recognizes and interacts with, enabling its catalytic role. We further investigated RumM catalysis in conjunction with the formation of complexes observed between RumM and the chimeric GFP fusion protein. Results obtained suggested some insights into the catalytic mechanisms of class II lanthipeptide synthetases. Our data further indicated the presence of three thioether bridges, contradicting a previous report whose findings ruled out the possibility of forming a third ring in RumA. Modified preRumA* was activated in vitro by removing the leader peptide using trypsin and biological activity was achieved against Bacillus subtilis ATCC 6633. A production yield of 6 mg of pure modified preRumA* per litre of E. coli culture was attained and considering the size ratio of the leader-to-core segments of preRumA*, this amount would generate a final yield of approximately 1-2 mg of active RumA when the leader peptide is removed. The yield of our system exceeds that attainable in the natural producer by several thousand-fold. The system developed herein supplies useful tools for product optimization and for performing in vivo peptide engineering to generate new analogues with superior anti-infective properties.